Newton's Law of Universal Gravitation

Written by Jerry Ratzlaff on . Posted in Classical Mechanics

All objects in the universe exert a gravitational force of attraction on each other.

 

Newton's Law of Universal Gravitation formula

\(\large{ F_g = G\; \frac{m_1 \;m_2}{r^2} }\)   

Where:

\(\large{ F_g }\) = gravitational force

\(\large{ r }\) = radius distance between objects

\(\large{ m_1 }\) = mass of object 1

\(\large{ m_2 }\) = mass of object 2

\(\large{ G }\) = universal gravitational constant

Solve for:

\(\large{ m_1 = \frac{ F_g \; r^2 }{ G \; m_2 }  }\)   
\(\large{ m_2 = \frac{ F_g \; r^2 }{ G \; m_1 }  }\)   
\(\large{ r = \sqrt { \frac{G\; m_1 \;m_2}{F_g} } }\)   

Tags: Equations for Gravity